Assessment of the Mobile Risk Source in Road Transport - Makka, Katarina; Stachova, Darina; Kampova, Katarina (Communications - Scientific letters of the University of Zilina, 2019)
Assessment of the mobile risk sources is not yet established in the European Union by law and therefore there is not enough pressure to manage and reduce risks. However, the transport of dangerous goods poses a special risk in terms of the nature of the transported material, especially for densely populated urban areas. The release of toxic or flammable substances into the air may endanger the health and life of many inhabitants. The assessment of consequences of the mobile accident hazards has been dealt with only seldom and not in details. The aim of this paper is to assess the risks associated with the transport of dangerous flammable substance. Authors would like to point out that the mobile resources represent a significant source of risk through the transport of dangerous goods in the event of an emergency occurrence associated with their leakage.